PERUBAHAN NILAI-NILAI KEMASYARAKATAN PADA CARITO ANAK MINANGKABAU (The Change of Community Values on Carito Anak Minangkabau) - Gayatri, Satya (Balai Bahasa Sumatra Barat, 2017)
This study aimed to describe the change of Minangkabau society values in Carito Anak Minangkabau. During the time, there are assumptions that Carito Anak Minangkabau is merely a fairy tale and monolithic. However, Carito can be interpreted according to the taste and ages. Carito was recorded from the memory conveyed by the active heir of three generations in a family (grandparents, parents, and child) in three Minangkabau areas, i.e darek, rantau, and pasisia. The carito text from the three generations are compared and focused on the dominant social problems in Minangkabau. It found that the changes in Carito Anak dealt with the changes in matrilineal systems from communal families to batih families, changes in understanding and implementation of Islam, and changes in motivation to migrate. Those dynamic changes are due to change of society that undergoaccording to the nature as a social being.